2010
DOI: 10.1007/s10409-010-0367-y
|View full text |Cite
|
Sign up to set email alerts
|

Performance of supersonic model combustors with staged injections of supercritical aviation kerosene

Abstract: Supersonic model combustors using two-stage injections of supercritical kerosene were experimentally investigated in both Mach 2.5 and 3.0 model combustors with stagnation temperatures of approximately 1,750 K. Supercritical kerosene of approximately 760 K was prepared and injected in the overall equivalence ratio range of 0.5-1.46. Two pairs of integrated injector/flameholder cavity modules in tandem were used to facilitate fuel-air mixing and stable combustion. For single-stage fuel injection at an upstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Recently, the staged fuel injection scheme has become a hot spot for the airbreathing hypersonic propulsion system [21][22][23] for it can improve the overall combustion performance of the scramjet combustor. Lai et al 24 have formulated a general sink-doublet model to predict the interaction of multiple tandem jets in a cross flow, and the predicted jet trajectory shows very good agreement with the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the staged fuel injection scheme has become a hot spot for the airbreathing hypersonic propulsion system [21][22][23] for it can improve the overall combustion performance of the scramjet combustor. Lai et al 24 have formulated a general sink-doublet model to predict the interaction of multiple tandem jets in a cross flow, and the predicted jet trajectory shows very good agreement with the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Norris [6] and Huang et al [7] proved the feasibility of using heated kerosene to improve the thrust. Recent experimental investigations [8][9][10] demonstrated that the use of supercritical kerosene injection holds the potential of enhancing fuel-air mixing and promoting overall burning in comparison with liquid fuel injections at similar fuel flow rates. However, a further increase in the fuel flow rate and the pressure rise with the singlestage injection was limited by the upstream propagation of boundary-layer separation due to excessive heat release [10].…”
mentioning
confidence: 99%
“…Recent experimental investigations [8][9][10] demonstrated that the use of supercritical kerosene injection holds the potential of enhancing fuel-air mixing and promoting overall burning in comparison with liquid fuel injections at similar fuel flow rates. However, a further increase in the fuel flow rate and the pressure rise with the singlestage injection was limited by the upstream propagation of boundary-layer separation due to excessive heat release [10]. The idea of staged fuel injection [11][12][13] uses the combustion of an upstream-injected fuel to improve the mixing and burning processes of the downstream-injected fuel while still keeping the fuel flow rate through the upstream injectors below the allowable value.…”
mentioning
confidence: 99%
“…Refs. [33,34]). If considering only high-temperature chemistry (> 900 K), such skeletal mechanisms can be further reduced.…”
Section: Skeletal Mechanism Of N-alkanes With Low-temperature Chemistrymentioning
confidence: 99%
“…Refs. [33,34]). Figure 8 indicates that the 72-species skeletal mechanism works quite well and the maximum discrepancy with the detailed mechanism is 31 %.…”
Section: Skeletal Mechanism Of a Kerosene Surrogatementioning
confidence: 99%